2018
DOI: 10.1080/17408989.2018.1470613
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising social justice and sociocultural issues within physical education teacher education: international perspectives

Abstract: Background: Physical education (PE) and physical education teacher education (PETE) have a substantial literature base that advocates for students to develop a critical consciousness, appreciate multiple perspectives, and engage in actions to enhance social justice (Tinning 2016). Analysing sociocultural issues, critically reflecting on beliefs, knowledge, biography and values, and developing a sense of agency to enact change, have been recognised as an integral part of the PETE knowledge base for some time (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…In this perspective, PSTs recognize the power structures in society that led to inequity and sought to empower students to challenge and change those inequities (O'Sullivan, 2018). Critical education cannot be reduced to a teaching method or transmission of knowledge as in a 'banking education' perspective (Freire, 1987); but rather should be viewed as an educational philosophy where a teacher concerned with questions of justice, democracy and ethics creates spaces for social change (Giroux, 2011;Hill et al, 2018;O'Sullivan, 2018).…”
mentioning
confidence: 99%
“…In this perspective, PSTs recognize the power structures in society that led to inequity and sought to empower students to challenge and change those inequities (O'Sullivan, 2018). Critical education cannot be reduced to a teaching method or transmission of knowledge as in a 'banking education' perspective (Freire, 1987); but rather should be viewed as an educational philosophy where a teacher concerned with questions of justice, democracy and ethics creates spaces for social change (Giroux, 2011;Hill et al, 2018;O'Sullivan, 2018).…”
mentioning
confidence: 99%
“…They found that particular programme 'values' take priority over others whereby a strong focus on the natural sciences can lead to a scientifically driven programme, which may be at the expense of more sociologically driven perspectives. Hill et al (2018) in their study of PETE in North America, Europe and Australasia found country-based differences in the ways in which social issues such as gender and race were problematised within programme constructions.…”
Section: Teacher Education Programme Development In Hpe: Contemporarymentioning
confidence: 99%
“…I want more classes that are geared toward physical education that are like this" (Intraview 2, Michael). As Curtner-Smith (1996) and Hill et al (2018) encouraged, PETE courses should focus on the political, social, moral, and ethical concepts of sport and physical education and PTs should be armed with tools to enact social justice. Subsequently, specific courses related to sociocultural issues and practical strategies are suggested or "you could go through your whole physical education program and not talk about social issues at all" (Intraview 2, Michael).…”
Section: (Intraview 2 Michael)mentioning
confidence: 99%
“…The limited amount of research conducted to date indicated that PETE faculty's efforts to employ transformative pedagogy have largely been ineffective in terms of convincing PTs to take a critical approach beyond their PETE (e.g., Curtner-Smith & Sofo, 2004;Gerdin, Philpot, & Smith, 2018;Hickey, 2001;Philpot, 2015;. In the United States, this may be because PETE faculty lack the training and content knowledge to implement such programs (Ruiz & Fernández-Balboa, 2005;Walton-Fisette et al, 2018) or have adopted neoliberal ideologies (Hill et al, 2018). In addition, some critically oriented American PETE faculty may have been ineffective because they worked in isoloation rather than as part of a team with the same focus (Flory & Walton-Fisette, 2015), or because their perspectives were countered and contradicted by more conservative colleagues (Cliff, 2012; and national teacher education policies (Ovens et al, 2018).…”
mentioning
confidence: 99%